Improving Coding Education with Storytelling Bakisah Bahasa Banjar for Elementary School Teachers - M. Saufi; Kamariah Kamariah; Haswinda Harpriyanti (Universitas Lambung Mangkurat, 2026)
Limited access to technological infrastructure and low teacher competency in coding instruction remain key challenges in implementing digital literacy in elementary schools in Banjar Regency. These conditions hinder the integration of computational thinking into classroom practices, particularly in schools with minimal digital resources. Therefore, this Community Service Program aimed to enhance teachers’ competencies in teaching coding through a culturally responsive approach as a solution to these challenges. This program adopted a Participatory Action Research (PAR) approach combined with Asset-Based Community Development (ABCD), emphasizing active teacher involvement and the utilization of local cultural assets. The intervention was implemented through three main stages: Unplugged Coding activities, integration of Bakisah Bahasa Banjar storytelling, and Scratch-based digital coding. A total of 22 elementary school teachers from the Ikatan Guru Kelas (IGK) of Banjar Regency participated in the program, followed by four post-training mentoring visits to support sustainable implementation. The results demonstrate significant improvements in three key outcome aspects: (1) increased teacher competency in understanding and applying basic programming concepts, (2) enhanced student learning interest through culturally contextualized coding activities, and (3) successful implementation of culture-based coding practices in classroom settings. In addition, the program established a digital teacher community that supports continuous professional development and sustainability. This program contributes to the development of culturally responsive coding education while promoting the preservation of local wisdom through technology-based learning. It also provides an alternative model for introducing coding in resource-limited educational contexts, fostering students who are both digitally literate and culturally aware.